2023
DOI: 10.3390/jof9020168
|View full text |Cite
|
Sign up to set email alerts
|

Functional Expression of Recombinant Candida auris Proteins in Saccharomyces cerevisiae Enables Azole Susceptibility Evaluation and Drug Discovery

Abstract: Candida auris infections are difficult to treat due to acquired drug resistance against one or multiple antifungal drug classes. The most prominent resistance mechanisms in C. auris are overexpression and point mutations in Erg11, and the overexpression of efflux pump genes CDR1 and MDR1. We report the establishment of a novel platform for molecular analysis and drug screening based on acquired azole-resistance mechanisms found in C. auris. Constitutive functional overexpression of wild-type C. auris Erg11, Er… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 66 publications
1
10
0
Order By: Relevance
“…Fluorescent microscopy utilizing Nile Red revealed that it is removed from yeast cells by specialized efflux pumps [ 14 ]. Using Nile Red, which was reported as a substrate for Cdr1p, Cdr2p, and CaMDR1p [ 30 ], it was determined if the fluconazole-resistant C. albicans strain was capable of removing this compound [ 14 , 31 ]. Candida ATCC strains that have been treated with Nile Red were able to continue retaining this dye, whereas fluconazole-resistant cells exhibited only a slight fluorescence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluorescent microscopy utilizing Nile Red revealed that it is removed from yeast cells by specialized efflux pumps [ 14 ]. Using Nile Red, which was reported as a substrate for Cdr1p, Cdr2p, and CaMDR1p [ 30 ], it was determined if the fluconazole-resistant C. albicans strain was capable of removing this compound [ 14 , 31 ]. Candida ATCC strains that have been treated with Nile Red were able to continue retaining this dye, whereas fluconazole-resistant cells exhibited only a slight fluorescence.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of small molecule inhibitors on a glucose-dependent efflux was previously studied with the help of Nile Red as a substrate for multidrug transporters overexpressed in S. cerevisiae [ 31 ]. In the current investigation, the evaluation of the activity of glucose-dependent efflux pumps showed the ability of photoactivated curcumin to inhibit pump-mediated Nile Red efflux.…”
Section: Discussionmentioning
confidence: 99%
“…The Nile Red efflux pump assay was performed as described previously [ 25 , 77 , 82 ]. Cells (grown to OD 600nm = 2) starved for 30 min at 30 °C with 2-DOG (5mM final concentration) were loaded with Nile Red (7.5 µM final concentration).…”
Section: Methodsmentioning
confidence: 99%
“…Instances of the CauErg11 K143R mutation have occasionally been found in clade II isolates [ 24 ]. Recombinant Sacharomyces cerevisiae strains expressing CauErg11 Y132 and CauErg11 K143R showed elevated minimum inhibitory concentration (MIC) values for FLC and Voriconazole (VRC) but not POS when compared to wild-type CauErg11 [ 25 ]. Gain-of-function (GOF) mutations in the transcriptional factor Upc2 up-regulate ergosterol biosynthesis genes in C. albicans , leading to Erg11 overexpression and FLC resistance [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation